Demographic Differences in Youth Perceptions of Staff: A National Evaluation of Adjudicated Youth - Pederson, Casey A. (International journal of offender therapy and comparative criminology, 2021)
Despite the large societal and personal cost associated with the detainment of juvenile offenders in residential facilities, little is known about the factors that contribute to youth behavior while incarcerated. One factor that may be of importance to maintaining security within facilities and improving rehabilitation efforts is youth’s perceptions of correctional staff, namely, youth’s perceptions of positive staff characteristics (e.g., friendliness; helpfulness) and staff behavior toward youth (e.g., fair punishments). Accordingly, the current study used the National Survey of Youth in Custody across two cohorts to better understand youth perceptions about staff by examining rates of these perceptions within juvenile detention centers nationwide. Furthermore, given the overrepresentation of marginalized groups in the justice system, systematic differences in youth’s perceptions about staff were evaluated based on demographic characteristics, including age, race, sex, and sexual orientation, to better understand how these characteristics influence youth perceptions. Results suggested several significant differences based on demographic characteristics, with the most prominent and consistent differences associated with race and age, with Black youth and older youth having the least positive views of staff. Interestingly, non-heterosexual youth were more likely to view staff characteristics as positive than heterosexual youth. Implications of findings are discussed.